Key player eaudiobook - Yang, Kelly (Front Desk, 2022)
Mia Tang is going for the goal in the fourth Front Desk novel by New York Times bestselling author Kelly Yang! The Women's World Cup coming to Southern California, everyone is soccer-crazy — especially Mia Tang! The U.S. is playing China in the finals, and Mia feels like her two identities are finally coming together. Less exciting, though? The fact that her P.E. teacher wants Mia to get out of the soccer field, too — or fall short of the grade she needs to earn a spot at journalism camp. But as always, Mia Tang is ready with a plan: she'll track down the two women's teams, interview them, and write an A-grade article for P.E. instead! It's not so easy, though, finding professional athletes in Pasadena — or bringing two identities together, even during a game. As Mia aims for her goals, she'll have to face prejudice, discrimination, and her own fears. But if anyone can find a way to win, it's Mia Tang!